Petri Nets for Systems Engineering A Guide to Modeling, Verification, and Applications - Girault, Claude; Valk, Rüdiger (Springer Berlin Heidelberg, 2003)
Formal methods for the specification and verification of hardware and software systems are becoming more and more important as systems increase in size and complexity. The aim of the book is to illustrate progress in formal methods, based on Petri net formalisms. It contains a collection of examples arising from different fields, such as flexible manufacturing, telecommunication and workflow management systems. The book covers the main phases of the life cycle of design and implementation of a system, i.e., specification, model checking techniques for verification, analysis of properties, code generation, and execution of models. These techniques and their tool support are discussed in detail including practical issues. Amongst others, fundamental concepts such as composition, abstraction, and reusability of models, model verification, and verification of properties are systematically introduced